Absence of HPV Infection Is Associated with Smoker Patients with Squamous Cell Carcinoma of the Oropharynx - Soares, Gláucia Resende (Hindawi Publishing Corporation, 2014)
The purpose of this study was to evaluate the survival of patients with SCC of the oropharynx, according to the presence of HPV and tobacco consumption. A total of 37 patients were followed up for at least 5 years after being diagnosed with SCC of the oropharynx. The biopsy tissue was submitted to the polymerase chain reaction (PCR) and in situ hybridization (ISH) methods for broad determination of HPV presence, to identify the presence of high-risk viruses (16 and 18). 12 of the 37 (32.4%) samples were HPV positive, whereas the two specific types of virus were identified in two samples for HPV-16 and in no samples for HPV-18. We observed no significant effect of the virus in survival analysis, irrespective of tobacco consumption. The level of tobacco consumption was significantly higher in the group of HPV-negative patients (P = 0.0283), in which all the patients in this group were smokers. Therefore, HPV did not change the survival of patients with SCC of the oropharynx in this study, indicating that factors other than tobacco need to be studied in conjunction with it, and the level of tobacco consumption is significantly higher in the group of HPV-negative patients.